Simulated litter input drives shifts in carbon allocation strategies within alpine meadows of the three rivers source region - Lin, Weishan; De, Kejia; Zhang, Lin; Xiang, Xuemei; Feng, Tingxu; Li, Fei; Wei, Xijie (Frontiers in Plant Science, 2026)
To reveal the transformation in carbon allocation strategies of alpine meadows in the Three Rivers Source Region under litter input.MethodsWe conducted an experimental study on litter input in alpine meadow in Chengduo County, Qinghai Province, with the following treatments: ungrazed (F), lightly grazed (L) and moderately grazed (M). Through systematic monitoring of plant community and soil microbial biomass, we revealed the mechanism of litter inputs on total plant community carbon pool (PCP) and microbial biomass carbon pool (MBCP).ResultThere were interactions between different grazing intensities and months in plant root biomass (RB), above ground community carbon content of Plant (AC), carbon content of root (RC), Plant root carbon pool (RCP), soil microbial biomass carbon (MBC), MBCP, easily oxidized organic carbon (EOC), soil nitrate nitrogen (NO3--N), and cellobiose hydrolase (CBH). The effects of month on above-ground plant community biomass (AGB), RB, AC, RC, RCP, MBC, MBCP, microbial biomass nitrogen (MBN), soil organic carbon (SOC), EOC, dissolved organic carbon (DOC), soil ammonium nitrogen (NH4+-N), NO3--N, glucose oxidase (GOD), -1, 4-glucosidase (S-β-GC), CBH, soil dehydrogenase (S-DHA), β-1, 4-xylosidase (XYS), and soil hydrolase (S-FDA) outweighed that of grazing intensity. Multiple regression results from the mixed effects model showed that DHA and GC explained 27.31% of the variation in PCP, while GOD and EOC explained 16.31% and 6.32% of the variation in MBCP, respectively. Structural equation modeling explained 35% and 65% of the PCP and MBCP variability.DiscussionThe effect of month on PCP, MBCP, organic carbon components and enzyme activity is greater than that of grazing intensity under litter input conditions. This study can help to reveal the shifts in carbon allocation strategies in alpine meadows driven by litter inputs and their ecological significance.